ICONIC study—conservative versus conventional oxygenation targets in intensive care patients: study protocol for a randomized clinical trial - Grim, CCA; van der Wal, LI; Helmerhorst, HJF; van Westerloo, DJ; Pelosi, P; de Jonge, E; Schultz, MJ (BioMed Central, 2022)
Background Oxygen therapy is a widely used intervention in acutely ill patients in the intensive care unit (ICU). It is established that not only hypoxia, but also prolonged hyperoxia is associated with poor patient-centered outcomes. Nevertheless, a fundamental knowledge gap remains regarding optimal oxygenation for critically ill patients. In this randomized clinical trial, we aim to compare ventilation that uses conservative oxygenation targets with ventilation that uses conventional oxygen targets with respect to mortality in ICU patients.